Stability, characterization and functionality of proton conducting NiO-BaCe0.85-xNbxY0.15O3-delta cermet anodes for IT-SOFC application - Zunic, Milan [UNESP]; Brankovic, Goran; Basoli, Francesco; Cilense, Mario [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2014)
There are many of properties of anodes based on proton conductors, like microstructure, conductivity and chemical stability, which should be optimized. In this work we were dealing with the influence of niobium on the chemical stability, microstructural and electrical characteristics of proton conducting NiO-BaCe0.85-xNbxY0.15O3-delta (NiO-BCNYx) anodes. Four anode substrates NiO-BCNYx of different Nb concentration were prepared using the method of evaporation and decomposition of solutions and suspensions (EDSS). Sintered anode substrates were reduced and their microstructural and electrical properties were examined before and after reduction as a function of the amount of niobium. Chemical stability tests showed strong influence of Nb amount on the chemical stability of anodes in the CO2. Microstructural properties of the anode pellets before and after testing in CO2 were investigated using X-ray diffraction analysis. Electrical properties of anode samples were examined by impedance spectroscopy measurements and the conductivity values of reduced anodes were more than 50 S cm (1) at 600 degrees C confirming percolation through Ni particles. Fuel cells were fabricated with aim to examine the functionality of anodes. During the fuel cell test the cell with Ni-BCNY10 anode achieved the highest performance, demonstrating a peak power density of 164 mW cm (2) at 650 degrees C, which confirmed the functionality of Ni-BCNY anodes. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: Anode; Fuel cells; Cermet; Protonic conductor; Thick film